A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber - Lin, Shan; Yao, Yunzhi; Ren, Dong (Zootaxa, 2018)
A new genus and species of the extinct family Weitschatidae, Criniverticillus longicumulus gen. et sp. nov. (Hemiptera: Coccomorpha), is described and illustrated from mid-Cretaceous Burmese amber. The new species is based on a fossil specimen with complete body, wings and antennae. The family diagnosis is updated to include similarities between Criniverticillus, Pseudoweitschatus and Weitschatus. An identification key to species of Weitschatidae is provided.